(untitled) (Research, Society and Development, 2021)
Metformin hydrochloride (MetCl) is used worldwide in the treatment of type-2 diabetes mellitus. Although extended-release (XR) tablets containing 500 mg, 850 mg, and 1000 mg of MetCl are marketed, it is not uncommon to split the tablet when the dosage form of the required strength is not available commercially. The aim of work was to evaluate the effects of splitting on the in vitro performance of XR tablets containing MetCl. We performed quality control assays and comparative dissolution profile studies among several medicines containing 500 mg and 1000 mg of MetCl, marketed in Brazil and Argentina. Tablets containing 1000 mg of MetCl were halved (test samples) and compared with whole tablets of products containing 500 mg of MetCl (reference samples). The halved tablets were more fragile and presented lower uniformity of mass and dosage unit as compared to the whole ones. However, it was evidenced by the F2 bootstrapping parameter that splitting MetCl XR tablets did not significantly impact the in vitro drug release profiles as compared to the whole tablets. In addition, nor the drug release mechanism neither the release kinetics were significantly affected. The XR tablets containing 1000 mg of metformin hydrochloride might be eligible for division, however, manufacturers could provide appropriate scores in the tablets surfaces to make the splitting proper and safer for the patients.